Influence of minimum inhibitory concentration in clinical outcomes of Enterococcus faecium bacteremia treated with daptomycin: Is it Time to change the breakpoint? (2016)
Background. Daptomycin has become a front-line antibiotic for multidrug-resistant Enterococcus faecium bloodstream infections (BSIs). We previously showed that E. faecium strains with daptomycin minimum inhibitory concentrations (MICs) in the higher end of susceptibility frequently harbor mutations associated with daptomycin resistance. We postulate that patients with E. faecium BSIs exhibiting daptomycin MICs of 3–4 µg/mL treated with daptomycin are more likely to have worse clinical outcomes than those exhibiting daptomycin MICs ≤2 µg/mL. Methods. We conducted a multicenter retrospective cohort study that included adult patients with E. faecium BSI for whom initial isolates, follow-up blood culture data, and daptomycin administration data were available. A central laboratory performed standardized daptomycin MIC testing for all isolates. The primary outcome was microbiologic failure, defined as clearance of bacteremia ≥4 days after the index blood culture. The secondary outcome was all-cause in-hospital mortality. Results. A total of 62 patients were included. Thirty-one patients were infected with isolates that exhibited daptomycin MICs of 3–4 µg/mL. Overall, 34 patients had microbiologic failure and 25 died during hospitalization. In a multivariate logistic regression model, daptomycin MICs of 3–4 µg/mL (odds ratio [OR], 4.7 [1.37–16.12]; P = .014) and immunosuppression (OR, 5.32 [1.20–23.54]; P = .028) were significantly associated with microbiologic failure. Initial daptomycin dose of ≥8 mg/kg was not significantly associated with evaluated outcomes. Conclusions. Daptomycin MICs of 3–4 µg/mL in the initial E. faecium blood isolate predicted microbiological failure of daptomycin therapy, suggesting that modification in the daptomycin breakpoint for enterococci should be considered.